Factors influencing employee turnover intention in the commercial banking sector in Kuala Lumpur - Doreen Shamala, Antonio Merino (2017)
Employees are most vital and valuable assets in all organization. An organization would not be able to achieve its success without the necessary support and dedication of its employees. This objective of this research is to identify the factors that influence turnover intention among the employees in the commercial banking sector in Kuala Lumpur by accessing the independent variables which are job satisfaction, empowerment, job stress and external job opportunity. The questionnaires were distributed to five banks who willingly participated in this research whereby three hundred seventy five bank employees participated in this research. The researcher chose the convenience sampling which falls under the non-probability sampling. Descriptive and inferential statistics were used to measure the relationship of the variables and to draw a conclusion between the independent and dependent variables. The findings revealed that there is existing relationship between job satisfaction, job stress, empowerment and employee turnover. On the other hand external job opportunity was not a significant predictor towards employee turnover. The independent variables only revealed 9.1% of the influences on employee turnover intention. Another pertinent factor could be the fact that the respondents have resigned to the fact that jobs are rare and therefore they choose to remain where they are in order to ride out the bad times and hope to move to greener pastures when times are better.